Effect of using two levels of bread yeast Saccharomyces cerevisiae on some economic traits of Arabian dam - Husam Ali Majeed Al-Zubaedi; Meitham K, Ali AL-Galiby (University of Thi-Qar Journal of agricultural research, 2021)
This study was conducted in the animal field of the College of Agriculture and the Marshes / University of Dhi Qar for the period from 11/6/2020 to 16/2/2021. In this experiment, (12) Arabi dairy sheep were used with their lambs ranging in age from one and a half to two years, single and close in birth. The times of their birth, and their average initial weights were (43.90, 48.50, 44.60) kg for the first, second and third treatments, and after giving the ewes a preparatory stage for two weeks, the ewes and their lambs were randomly distributed between three treatments (nutrition) equally, and each treatment was four replicates, and the ration was given to the ewes on the basis of 3% The ewes of the first treatment were fed a control ration consisting of (25% barley, 25% wheat bran, 20% crushed corn, 20% flour, 7% soybean meal and 3% salt) and the second treatment (basic ration + 3 gm yeast /head /day) and the third treatment (basic diet + 5 gm yeast /head/day) and straw was provided freely to all the mothers of the different treatments.The weights, weight increases and the amount of feed consumed were recorded. Presence Excellence moral (0.05≥P) inThe lambs weighed, and there was a moral superiority 0.05≥P) in the second week of the experiment only for the treatment (3 gm yeast / head / day) Its value was (16.47) kg compared toworth transactions, while There are no significant differences in the rate of total and daily weight gain of lambs in all treatments Experience On Although there was an arithmetic increase in favor of the treatment (5 gm yeast /head /day).